7Beta-OH-DHEA counteracts dexamethasone induced suppression of primary immune response in murine spleenocytes - Sterzl, I; Hampl, R; Sterzl, J; Votruba, J; Stárka, L (The Journal of steroid biochemistry and molecular biology, 1999)
The effect of dexamethasone and of three potential antiglucocorticoids, namely dehydroepiandrosterone (DHEA) and its 7alpha-and 7beta-hydroxylated metabolites, on primary immune response has been studied by measuring the number of plaque forming cells (NPFC) and their viability in a cell culture of murine spleenocytes. As expected, dexamethasone suppressed considerably the NPFC as well as their viability. Surprisingly, DHEA as well as its 7alpha-hydroxylated metabolite decreased significantly the NPFC, while the effect of 7beta-hydroxy-DHEA was different: at low doses it decreased the NPFC, but this effect was less pronounced at higher concentrations. In addition, 7beta-hydroxy-DHEA was able to counteract the effect of dexamethasone on the NPFC. None of the natural steroids affected the cell viability.
Keywords: dexamethason; Antibody-Producing Cells; Mice, Inbred BALB C; Spleen; slezina; In Vitro Techniques; Dexamethasone; Cell Survival; vztah mezi dávkou a účinkem léčiva; techniky in vitro; hemolytická plaková technika; myši; Dehydroepiandrosterone; Dose-Response Relationship, Drug; Mice; viabilita buněk; myši inbrední BALB C; zvířata; dehydroepiandrosteron; Animals; buňky produkující protilátky; Hemolytic Plaque Technique